Pengaruh Opini Audit Laporan Keuangan Pemerintah Daerah terhadap Kesejahteraan Masyarakat di Daerah - Widha Adinata; Teguh Puspandoyo; Mei Ling (Indonesian Treasury Review: Jurnal Perbendaharaan, Keuangan Negara dan Kebijakan Publik, 2023)
One of the principles of good governance is accountability, as reflected in Unqualified Audit Opinions. Accountability of government performance is expected in the improvement of public welfare. Regional governments have increasingly received Unqualified Audit Opinions on their financial statements, which reflects increasing quality of regional financial management and governance. Recent public discussions have questioned whether or not unqualified audit opinions have impact on public welfare. This study examines the impact of audit opinions, including the impact of successive Unqualified Opinion on HDI, using a Panel Regression model on all provinces data in Indonesia for the period of 2011—2019. Based on the REM estimation, this study concludes that the current audit opinion does not have impact on HDI because there is a time lag between the realization of spending and the increase in HDI. HDI is influenced by the accumulation of better audit opinions and the percentage of audit findings. Furthermore, the follow-up to audit recommendations does not impact HDI because it is merely a corrective action that would have more impact on current and future regional financial management policies and systems.